An Overview of the Problems and Prospects for Circular Agriculture in Sustainable Food Systems in the Anthropocene - Grumbine, R. Edward; Xu, J.C.; Ma, L. (Maximum Academic Press, 2021)
In this overview paper, we outline and explore problems and prospects for circular agriculture’s contributions to transformative change toward sustainable food systems in the Anthropocene. We define circular agriculture (CA) and provide historical context on its development. We then discuss how CA can contribute to food system transformations in four key areas: multi-functional landscapes; sustainable intensification (focusing on nitrogen/crop-livestock management and digital agriculture); smallholder farmers; and dietary change. We find that food systems transitions will be challenging due to the depth, scale, and speed of changes necessary for humans to remain within safe planetary boundaries out to 2050.